Efisiensi Belanja Pemerintah Terhadap Indeks Pembangunan Manusia Secara Regional di Indonesia - Indra Kurniawan; Murtala Murtala; Reza Juanda (LPPM UNIMAL, 2020)
This study analyzed the efficient level for Government expenditure on the regional Human Development Index (HDI) in Indonesia in 2014-2018. This study used panel data with the number of DMUs in 34 provinces in Indonesia, while the input variable was government spending in the health, education, economy, social protection sectors, and the output variable was the human development index for 2014-2018. This study used Data Envelopment Analysis (DEA) testing and focused on input (input-oriented) by using the assumption of Variable Return to Scale (VRS). The results showed that only 14 provinces were efficient in using Government Expenditures to increase HDI, but 20 provinces were inefficient in using Government Expenditures to increase HDI. Thus it is hoped that all provinces, especially those who were inefficient, can improve their performance in the use of government expenditure budgets that have been used in increasing the HDI value and the government can make decisions or policies in the problem of achieving the HDI value for each province in Indonesia.